In the Realm of the Scheme: The Limits of Interpretation of Archaic Greek Visual Culture - Wawrzyniec Miścicki (Ksiegarnia Akademicka Publishing, 2017)
The aim of this paper is to examine the possibilities of interpretation using readings of pictorial schemes on Archaic Greek vases on the example of a black-figure lekythos from the collection of the Institute of Archaeology of the Jagiellonian University in Krakow. The current interpretation of the scene on the vase describes it as setting out for the hunt. It is argued here that this scene represents warriors setting out for war, in line with the first interpretation of this piece made by Piotr Bieńkowski. Furthermore, it is argued that since the readings could always be plural, the creator of the vase made deliberate attempts to limit interpretation, however, the vase can still retain its interpretational freedom if put in a viewing context that stimulates unorthodox readings.